THE EFFECT OF CANDESARTAN PRE-STROKE USE ON THE FUNCTIONAL OUTCOME OF POST ISCHEMIC STROKE PATIENTS IN BETHESDA HOSPITAL YOGYAKARTA - Lise Insani Gulo; Rizaldy Taslim Pinzon; Esdras Ardi Pramudita (Sanata Dharma University, 2018)
Stroke is a leading cause of death and disability, where the main risk factor is hypertension. Angiotensin Receptor Blocker (ARB) is the most common drug for stroke prevention in high-risk hypertensive patients. The purpose of this study was to see whether the candesartan pre-stroke use can improve the functional outcomes of post ischemic stroke patients. The data were obtained from 191 retrospective observational studies. Data were collected from Stroke Registry and medical record at Bethesda Hospital Yogyakarta in 2014-2016, then analyzed univariate, followed by bivariate analysis using chi-square test, independent t-test and fisher exact test for the variable which has actual count (F0), and logistic regression for multivariate analysis. One hundred and ninety one samples were systematically reviewed to evaluate the effect of candesartan pre-stroke use on functional outcomes of post ischemic stroke patients in Bethesda hospital Yogyakarta whose range of ages was mostly between 61 and 70 years (30.9%) and were mostly male patients (56.5%). Patients with good functional outcomes (2) were 79.6% and poor functional outcomes (?2) were 20.4%. The results of bivariate analysis showed that candesartan did not affect the improvement of clinical outcome (OR: 1.806, 95% CI: 0.591-5.519, p: 0.294), and also not better than other angiotensin receptor blocker (p=0.505, OR=1.472, 95% CI= 0.470-4.611). The multivariate analysis showed that sex (OR: 0.366, 95% CI: 0.156-0.858, p: 0.021), loss of consciousness (OR: 0.107, 95% CI: 0.021-0.549, p: 0.007), limb weakness (OR: 0.236, 95% CI: 0.067-0.834, p: 0.025), dyslipidemia comorbidity (OR: 2.750, 95% CI: 1.177-6.427, p: 0.019) and aphasia (OR: 0.342, 95% CI: 0.107-1.100, p: 0.072) affected the functional outcome. The candesartan pre-stroke use did not improve the functional outcome of post ischemic stroke patient.